2013
DOI: 10.1103/physrevb.88.045413
|View full text |Cite
|
Sign up to set email alerts
|

Light emission and finite-frequency shot noise in molecular junctions: From tunneling to contact

Abstract: Scanning tunneling microscope induced light emission from an atomic or molecular junction has been probed from the tunneling to contact regime in recent experiments. There, the measured light emission yields suggest a strong correlation with the high frequency current/charge fluctuations. We show that this is consistent with the established theory in the tunneling regime, by writing the finite-frequency shot noise as a sum of inelastic transitions between different electronic states. Based on this, we develop … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…Such a difference between the left and right autocorrelators is also reported in Refs. [28,39]. Its origin is the distinct energy of the carriers contributing to S LL (ω) or to S RR (ω) when transferred through the junction (ε − ω versus ε).…”
Section: A Nsff Noise In Left and Right Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a difference between the left and right autocorrelators is also reported in Refs. [28,39]. Its origin is the distinct energy of the carriers contributing to S LL (ω) or to S RR (ω) when transferred through the junction (ε − ω versus ε).…”
Section: A Nsff Noise In Left and Right Reservoirsmentioning
confidence: 99%
“…Here we show that it makes sense to interpret each contribution to the NSFF auto-correlators in terms of the energy-transfer process, following the ideas developed by several authors. Indeed, it has been shown that the frequency at which the NSFF noise is evaluated corresponds to the energy provided or absorbed by the detector 14 or by the electromagnetic environment, and that current fluctuations produce radiation of photons/plasmons in a phase-coherent conductor [30][31][32][33][34][35][36][37][38][39][40][41][42] . To address this issue from a theoretical point of view, one can use either the scattering theory [43][44][45][46] or the non-equilibrium Green function (NEGF) technique 47,48 .…”
Section: Introductionmentioning
confidence: 99%
“…However, at higher conductance G > ∼ 0.5 G 0 , significant deviations appear. To explain the discrepancy, we consider the opening of additional channels with increasing conductance which has previously been observed in Ag and noble metal contacts [39][40][41][42]. In addition, they presumably are the reason for observed deviations of the 1e yield from a simple F ∼ 1 − τ behavior in Ag and Cu contacts [12,43].…”
mentioning
confidence: 93%
“…This field has been revived when it was observed that scanning tunneling microscopes (STM) tips can emit light with a significantly improved efficiency [3][4][5][6]. Many different theoretical studies have been devoted to this topic [7][8][9][10][11][12], and it is now well understood that the light emission process involves two steps: (i) inelastic tunneling, which generates a fluctuating electrical current, and (ii) photon emission by the time-dependent fluctuations. Yet, the efficiency remains very low-typically lower than one photon per 10 4 electrons-so that inelastic tunneling has not become a practical source of light.…”
mentioning
confidence: 99%